Efficacy of acupuncture for anxiety and depression in functional dyspepsia: A systematic review and meta-analysis. - Zhiwei Xu; Xuecheng Zhang; Hongshuo Shi; Minghao Liang; Fenglan Ning; Qi Wang; Hongling Jia (PLoS ONE, 2024)
Objective To assess the effectiveness of acupuncture for treating depression and anxiety in patients diagnosed with functional dyspepsia (FD). Methods PubMed, Embase, Cochrane Library, Web of Science, CNKI, Wanfang Data, Sinomed, and VIP Database were searched until April 30, 2023 for Randomized Controlled Trials (RCTs) comparing acupuncture to placebo or drugs for symptom alleviation. Two independent reviewers conducted the study search, data extraction, and bias risk assessment using the Cochrane Risk of Bias tool. Mean difference (MD), risk ratio (RR), and corresponding 95% confidence intervals (CI) were computed. Subgroup and sensitivity analyses were also performed. The Grading of Recommendations Assessment, Development, and Evaluation (GRADE) system was employed to evaluate the evidence level. Results A total of 16 RCTs involving 1315 participants were included. Acupuncture demonstrated marked superiority over placebo (MD = -7.07, 95%CI: -11.03 to -3.10, very low quality evidence) in mitigating Self-Rating Anxiety Scale (SAS) scores and was found to be more effective in reducing Self-Rating Depression Scale (SDS) scores than either placebo (MD = -4.63, 95%CI: -6.28 to -2.98, low quality evidence) or first-line drugs (MD = -2.71, 95%CI: -5.19 to -0.23, very low quality evidence). In terms of attenuating Hamilton Anxiety Rating Scale (HAMA) and Hamilton Depression Rating Scale (HAMD) scores, acupuncture consistently outperformed both placebo (HAMA: MD = -2.58, 95%CI: -4.33 to -0.83, very low quality evidence; HAMD: MD = -1.89, 95%CI: -3.11 to -0.67, low quality evidence) and first-line drugs (HAMA: MD = -5.76, 95%CI: -10.18 to -1.35, very low quality evidence; HAMD: MD = -5.59, 95%CI: -7.59 to -3.59, very low quality evidence). However, no significant difference was observed between acupuncture and placebo in terms of improvement in Hospital Anxiety and Depression Scale (HADS) scores. Conclusions Based on current clinical evidence, acupuncture might have a positive effect on depression and anxiety in patients with FD. Further large-sample, multi-center, high-quality RCTs validation are required, as the conclusion is limited by the quantity and quality of the included studies.